How to get to heaven from Colorado, and other essays - Chellman, Dana, author; Sloane, Sarah, advisor; Thompson, Deborah, advisor; Leck, Christopher, committee member (Colorado State University. Libraries, 2017)
A collection of eleven personal essays, this creative nonfiction masters thesis explores patterns and evolution of mental health and illness primarily as they exist within families and self. Using nonfiction forms including personal reflections, braided essays, collage essays, and flash nonfiction, the thesis anchors its essays in the precise visual images of place provided in maps of space, jigsaw puzzles, gazetteers, and an atlas of the human brain. The collection relies on historical renderings of brain and mind, X-rays of canine bodies, and images generated by Magnetic Resonance Imaging (MRIs) or the European Space Agency, for example, to show the machines and processes of assembling evidence and constructing partial records of mind and body. One major preoccupation or theme of the collection is the question of what happens when these constructions, which we put so much faith and trust into, break.